Przygotowanie do małżeństwa oraz towarzyszenie młodym małżonkom poprzez budzenie wiary potrzebą chwili. Na kanwie przemówienia Franciszka do Roty Rzymskiej z 21 stycznia 2017 roku - Góralski, Wojciech (Ius Matrimoniale, 2017)
The speech (fourth so far) given on 21 of January 2017 by Pope Francis to the Tribunal of the Roman Rota constitutes an important element of papal Magisterium in the important area of the life and activity of the Church, namely marriage and family. This time, the Holy Father focused on those preparing for marriage and young spouses. Considering the task of awaking and reviving faith both in the former and the latter, he expressed a view that the relationship between marriage and faith, two closely related realities, not only involves the juridical, but also theological dimension. Therefore, a concluded marriage should be both important, but also fruitful. In the Pope’s opinion, Christian communities, above all parish ones, play an especially important role in awakening and reviving faith in bridegrooms-to-be and young spouses.